Crustal attenuation structure of the Tianshan tectonic belt and its spatiotemporal variations - Li, Jin; Jiang, Haikun; Wang, Qiong (Frontiers in Earth Science, 2023)
The quality factor value (Q) of the crustal medium, which can describe the anelasticity within the Earth’s interior, is a sensitive indicator of changes in the crystalline structure induced by temperature and phase transformations. Although the velocity structure of the Tianshan region in Central Asia has been extensively studied, studies regarding its Q values are limited. These studies focus mainly on the crustal attenuation structure of the Tianshan region; however, their results are limited to the qualitative analyses of the local areas or averages over large areas. Therefore, in this study, we conducted seismic attenuation tomography to create a Q map of the crust underneath the Tianshan tectonic belt (TTB) at a resolution of 0.8° × 0.8° using data from 24,273 near-source waveforms recorded by 51 observation stations of the Xinjiang regional seismic network from 2009 to 2020. The regional distribution of the static and sliding-average values (QS) was calculated. The average value (Q0) of TTB was approximately 523. Additionally, Qs exhibited considerable lateral variations that strongly correlate with the surface tectonics of the TTB region. Furthermore, the velocity and attenuation structures of the TTB were positively correlated. The main part of the TTB exhibited high velocities and Q (indicating low attenuation), whereas the areas adjoining the Tarim and Junggar basins (at the South and North of the TBB, respectively) and their margins exhibited low velocities and Q (indicating high attenuation). This suggested that the attenuation structure of the TTB was highly consistent with its velocity and density structures. Since 1900, most earthquakes in the TTB having magnitudes ≥6.0 earthquakes have occurred at the junctions of high- and low-Q-value areas, or in areas with low Q values. According to the Qs values in different periods, the average Qs of the entire TTB only varied between 500 and 540. However, the average Qs in the middle TTB region portrays an upward trended over time (from 494 in 2010 to 554 in 2020). The average Qs of the southwestern TTB region has been relatively stable, varying between 490 and 530. The Q0 of the southwestern TTB region was lower than that observed in the middle TTB region in most of the time. This observation is more consistent with the tectonic activity recorded in the southwestern TTB region (with greater intensity) than that observed in the middle Tianshan. In addition, the number of earthquakes with magnitudes ≥4.0 correlated positively with the regional average Qs in the middle and southwestern Tianshan. Notably, the higher the regional average Q value, the larger the number of moderate earthquakes. This correlation suggests that in earthquake-prone regions, the accumulation and release of stress influence the opening or closure of crustal fractures, resulting in noticeable changes in the Q values. The findings of our study provide novel insights into the mechanisms of earthquakes and their correlation with the structure of the Earth’s crust.